Raised Imperishable: The Ethics of the Bodily Resurrection - Page, Kaylie G. (Lumen et Vita, 2019)
Christians live in light of eternity: we anticipate a future glory yet to be unveiled, but we also have some level of participation in that glory in the present. What shape should that anticipation and participation take? In other words, how does the resurrection influence ethical choices in the present? This paper draws on the work of historical and modern theologians to consider what effects the resurrection of the body has on Christian life in the present. It argues that the nature of embodied life in the resurrection affects our view of and our behavior towards our own bodies, the body of the church, and the bodies of other people in the world. While the paper sketches the outlines of an ethic based on the bodily resurrection in each of these areas, its main concern is with the spiritual attitude that informs and results from these ethical choices. As Dietrich Bonhoeffer observes, Christian ethics that focuses on the resurrection tends to fall into one of the two traps of otherworldliness or secularism. However, when attention is given to the spiritual effects of a resurrection-oriented ethic, both of these pitfalls can be avoided. Living in light of the resurrection sharpens our anticipation of heavenly glory, but it also proves our inability to attain that glory by our own power, forcing us to rely ever more on God as the source of our salvation. Thus, although living with reference to the resurrection of the body has positive influence on our ethical choices, the primary impact of such a life is to drive the Christian back to the Gospel.